Solvent-Controlled Polymerization of Molecular Strontium Vanadate Monomers into 1D Strontium Vanadium Oxide Chains - Schwarz, Benjamin; Dürr, Maximilian; Kastner, Katharina; Heber, Nora; Ivanovic-Burmazovic, Ivana; Streb, Carsten (Inorganic Chemistry, 2019)
We report the polymerization of a solvent-stabilized molecular strontium vanadium oxide monomer into infinite 1D chains. Supramolecular polymerization is triggered by controlled solvent-exchange, which leads to oligomer and polymer formation. Mechanistic insights into the chain formation were obtained by solid-state, solution, and gas-phase studies. The study shows how reactivity control of molecular metal oxides can be used to assemble complex inorganic polymeric structures.
CRIS-Team WoS Importer:2019-09-20